Troubleshooting ocular prosthesis: A case series - Sivaranjani Gali; V Midhula; Anita Naimpally; Hima B Lanka; Keerthy Meleppura; Chinmaya Bhandary (Wolters Kluwer Medknow Publications, 2022)
This case series reports on clinical challenges faced during the rehabilitation of custom ocular prosthesis. Each of these cases relate the challenges of making ocular impressions for an improved retention and support of ocular prosthesis and presents the significance of scleral contouring in overcoming cosmetic defects of the eye. In addition, evaluation of scleral wax pattern, methods of iris location and scleral characterization methods in ocular rehabilitation are further discussed.